Factores de riesgo y su influencia en la neumonía, en niños menores de 5 años que acuden al hospital Martin Icaza, Babahoyo Los Ríos, periodo mayo a octubre 2018. - Leon Suarez, Karen Abigail (2018)
Pneumonia is a pathology with great relevance in the hospital setting, which is characterized by inflammation of the lung parenchyma, and pulmonary infiltrates in diagnostic studies, this disease also triggers a problem within the area of health and is considered a disease very prevalent, which can be fatal mainly for more susceptible groups such as children under 5 years. The objective of this research is to determine the risk factors that influence pneumonia to reduce morbidity and mortality in children under 5 years of age who attend the Martin Icaza Roldós Hospital in the period from May to October 2018. It is an observational research, descriptive-explanatory, to determine the most influential risk factors in pneumonia. For the collection of data, a survey was used to address the mothers of children under 5 years of age who attend the General Icaza Hospital. As a tool, a questionnaire was created where the different variables under investigation were explored. Population and shows a total of 92 children who suffered from PNEUMONIA in the period May to October 2018 were chosen using the inclusion and exclusion criteria. With this research it was possible to determine that the children who suffered the most from PNEUMONIA were those from 0 to 2 years old, of marginal urban residence, overcrowded, with low birth weight, low income.